Extracellular microRNAs profile in human follicular fluid and IVF outcomes. Issue 1 (December 2018) - Martinez, Rosie; Liang, Liming; Racowsky, Catherine; Dioni, Laura; Mansur, Abdallah; Adir, Michal; Bollati, Valentina; Baccarelli, Andrea; Hauser, Russ; Machtinger, Ronit
Abstract Encapsulated microRNAs (i.e., miRNAs within the extracellular vesicles, i.e., EV-miRNAs) have been detected in follicular fluid in both animal and human studies and different profiles have been associated with IVF cycle characteristics. However, limited studies to date have investigated other IVF outcomes, including fertilization status and embryo quality on day three". In this cohort, we performed a cross-sectional analysis on 126 women who contributed follicular fluid from a single follicle during a single IVF cycle. One hundred and ninety-two EV-miRNAs were assessed by univariable fold-change and multivariable logistic regression analyses. Hsa-miR-92a and hsa-miR-130b, were over-expressed in follicular fluid samples from oocytes that failed to fertilize compared to those that were normally fertilized. Additionally, hsa-miR-888 was over-expressed and hsa-miR-214 and hsa-miR-454 were under-expressed in samples that resulted in impaired day-3 embryo quality compared to top-quality day-3 embryos. After adjusting for confounders as BMI, smoking and total motile sperm, associations of these EV-miRNAs remained significant. In-silico KEGG pathway analyses assigned the identified EV-miRNAs to pathways of follicular growth and development, cellular signaling, oocyte meiosis, and ovarian function. Our findings suggest that EV-miRNAs may play a role in pathways of ovarian function and follicle development, which could be essential for understanding the molecular mechanisms that could lead to a successful pregnancy and birth.